Environmental chemistry - Manahan, Stanley E. (CRC Press, 2010)
The field of environmental chemistry has evolved significantly since the publication of the first edition of Environmental Chemistry. Throughout the book's long life, it has chronicled emerging issues such as organochloride pesticides, detergent phosphates, stratospheric ozone depletion, the banning of chlorofluorocarbons, and greenhouse warming. During this time the first Nobel Prize for environmental chemistry was awarded. Written by environmental chemist Stanley Manahan, each edition has reflected the field's shift of emphasis from pollution and its effects to its current emphasis on sustainability. What makes this book so enduring? Completely revised, this ninth edition retains the organizational structure that has made past editions so popular with students and professors while updating coverage of principles, tools, and techniques to provide fundamental understanding of environmental chemistry and its applications. It includes end-of-chapter questions and problems, and a solutions manual is available upon qualifying course adoptions. Rather than immediately discussing specific environmental problems, Manahan systematically develops the concept of environmental chemistry so that when he covers specific pollutions problems the background necessary to understand the problem has already been developed.